The Influences of Political Values Manifested in Advertisements on Political Participation: Moderating Roles of Self-transcendence and Conservation. (November 2020) - Raza, Syed Hassan; Adamu, Adamu Abbas; Ogadimma, Emenyeonu C.; Hasnain, Amna
This study seeks to explain how political participation is influenced by cultural values manifested in political advertising. In this regard, this study proposes a model that encompasses the concepts of Schwartz' basic human values in which self-transcendence and conservation interact with three political values manifested in advertisements, namely law and order, civil liberties and patriotism, to determine political participation. Analyses were performed on a random sample of 834 Pakistanis collected through a survey. Structural equation modelling (SEM) techniques were employed, and analysis of moment structures (AMOS) was used to determine political participation. The findings of this study revealed that self-transcendence and conservation, albeit varied intensity, interact with political values manifested in advertisements. The findings also provide theoretical and managerial implications, which are discussed in greater detail in this article.